Performance and comparison of different phasor calculation techniques for the power system monitoring - Ravi Ponnala; Muktevi Chakravarthy; Suraparaju Venkata Naga Lakshmi Lalitha (Bulletin of Electrical Engineering and Informatics, 2022)
Day to day to electrical power demand increases very rapidly with linear and non-linear load demands. Especially the nonlinear loads are creating the harmonics in the current and voltage signals. The current and voltage signal values are measured with the phasor measurement unit (PMU) for the proper magnitude and phase angle calculation even in the presence of harmonic components in the signals. The performance of the PMU is depending upon the phasor calculation technique. Different technique/methods are available for the phasor calculation, from the method to method there is difference in the accuracy, phasor computation time and complexity. In this paper various techniques for phasor calculation are presented. For better performance of PMU, more accurate and less computation time for phasor calculation technique is required. But in real time, accuracy and speed both may not satisfied with single technique. Need to find a satisfactory technique, which satisfies the speed of phasor computation and accuracy. In this paper it is proposed that direct phasor estimation technique, which gives the better results in terms of accuracy and time and this method, satisfies the requirements for the dynamic monitoring of power system according to the IEEE std. C37.118.1-2011.